Potassium Carbonate Assisted Synthesis Of α, β, γ, δ-Unsaturated Ketones - Kulkarni, Pramod; Gawade, Sammer (Київський національний університет імені Тараса Шевченка, 2020)
The Cinnamylideneacetophenones derivative is shows important medicinal properties and intermediate in organic synthesis.  Several substituted α, β, γ, δ-Unsaturated Ketones were prepared in high yield and purity by direct reaction of substituted cinnamaldehyde and ketones in the presence of potassium carbonate as a base in ethanol at 50ºC. The merit of the method is short reaction times, high yield, easy work-up and purification process, inexpensive and easily available catalyst.
Keywords: Potassium carbonate; Unsaturated ketones; Claisen-Schmidt reaction; Condensation; Ethanol